Brain abscess in Iraq during a 10 years period: Part 1. Epidemiology, aetiology and clinical picture - Al-Tamimi, Zahra'a A.J.; Al-Hadithi, Tariq S.; Al-Khalili, Abdul- Hadi; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: This study comprises two parts. "['his part deals with epidemiology, aetiology and clinical features of brain abscess during a 10 years period, while the second will dealwith diagnostic investigation, management and final outcome of brain abscessMethods: The case records of patients with brain abscess admitted to the neurosurgical specialties hospital in Baghdad over a 10 years period extending from 1" Jan. 1993 to 31S`Dec. 2002, inclusive were reviewed. Data obtained included demographic and clinical data.Results: A total of 78 cases (1.2% of total admission) of brain abscess were admitted. Their age ranged from one month to 68 years. The most common' aetiological (actor was cyanoticheart disease, with the congenital anomaly being unrepaired in all cases. Remote infection foci other than heart represent minority. Half of the cases had a rapid onset and fluminantprogression. The presenting features of the patients older than one year were raised intracranial pressure, and focal neurological deficit and infection.Conclusion: Maintaining a high index of clinical suspicions in patients having one of the infection sources together with neurological signs should be emphasized. '.